Doping Process of 2D Materials Based on the Selective Migration of Dopants to the Interface of Liquid Metals. Issue 43 (12th September 2021) - Ghasemian, Mohammad B.; Zavabeti, Ali; Mousavi, Maedehsadat; Murdoch, Billy J.; Christofferson, Andrew J.; Meftahi, Nastaran; Tang, Jianbo; Han, Jialuo; Jalili, Rouhollah; Allioux, Francois‐Marie; Mayyas, Mohannad; Chen, Zibin; et al.
Abstract: The introduction of trace impurities within the doping processes of semiconductors is still a technological challenge for the electronics industries. By taking advantage of the selective enrichment of liquid metal interfaces, and harvesting the doped metal oxide semiconductor layers, the complexity of the process can be mitigated and a high degree of control over the outcomes can be achieved. Here, a mechanism of natural filtering for the preparation of doped 2D semiconducting sheets based on the different migration tendencies of metallic elements in the bulk competing for enriching the interfaces is proposed. As a model, liquid metal alloys with different weight ratios of Sn and Bi in the bulk are employed for harvesting Bi2 O3 ‐doped SnO nanosheets. In this model, Sn shows a much stronger tendency than Bi to occupy surface sites of the Bi–Sn alloys, even at the very high concentrations of Bi in the bulk. This provides the opportunity for creating SnO 2D sheets with tightly controlled Bi2 O3 dopants. By way of example, it is demonstrated how such nanosheets could be made selective to both reducing and oxidizing environmental gases. The process demonstrated here offers significant opportunities for future synthesis and fabrication processes in the electronics industries. Abstract : The interface of liquid metals is used as natural filtering for doping and harvesting 2D doped metal oxide semiconductors. 2D Bi2 O3 ‐doped SnO semiconducting sheets are produced based on the different migration tendencies of Sn and Bi metals within the bulk competing for the selective enrichment of the liquid metal interface.